2009
DOI: 10.1007/s10530-009-9670-6
|View full text |Cite
|
Sign up to set email alerts
|

Determining the impact of scale insect honeydew, and invasive wasps and rodents, on the decomposer subsystem in a New Zealand beech forest

Abstract: Relatively few studies have considered how aboveground invasive consumers influence decomposer communities. We investigated the potential effects of three types of animals on the decomposer subsystem in a floristically simple New Zealand Nothofagus forest. These animals are the native beech honeydew scale insect (Ultracoelostoma spp.) that secretes large amounts of sugar-rich honeydew that washes to the soil, invasive social wasps (Vespula spp.) that remove honeydew and prevent it from reaching the ground, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 60 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…For example, Vespula vulgaris is implicated in the longterm decline of several species of common birds in these forests (Elliott et al 2010). In addition to affecting the above-ground forest community, these wasps have multitrophic impacts on the soil food web (Wardle et al 2010). By disrupting the addition of honeydew to the forest floor, wasps can alter multiple components of the soil decomposer subsystem, including decreasing litter decomposition (Wardhaugh and Didham 2006;Wardle et al 2010) and altering soil carbon sequestration and nutrient capital (Wardle et al 2010).…”
Section: Invasive Alien Vespula Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Vespula vulgaris is implicated in the longterm decline of several species of common birds in these forests (Elliott et al 2010). In addition to affecting the above-ground forest community, these wasps have multitrophic impacts on the soil food web (Wardle et al 2010). By disrupting the addition of honeydew to the forest floor, wasps can alter multiple components of the soil decomposer subsystem, including decreasing litter decomposition (Wardhaugh and Didham 2006;Wardle et al 2010) and altering soil carbon sequestration and nutrient capital (Wardle et al 2010).…”
Section: Invasive Alien Vespula Speciesmentioning
confidence: 99%
“…In addition to affecting the above-ground forest community, these wasps have multitrophic impacts on the soil food web (Wardle et al 2010). By disrupting the addition of honeydew to the forest floor, wasps can alter multiple components of the soil decomposer subsystem, including decreasing litter decomposition (Wardhaugh and Didham 2006;Wardle et al 2010) and altering soil carbon sequestration and nutrient capital (Wardle et al 2010). Of particular note, a four-year experiment showed that wasps may increase humus carbon sequestration by around 40%, indicating this IAS may have a large, widespread effect on ecosystem carbon dynamics (Wardle et al 2010).…”
Section: Invasive Alien Vespula Speciesmentioning
confidence: 99%
“…However, the evidence is far from equivocal. To date, there is evidence that the readily available carbon (C) present in honeydew can increase the total supply of nitrogen via stimulation of free-living nitrogen-fixing soil bacteria (Petelle, 1984(Petelle, , 1980, reduce the amount of nitrogen in soil leachate (Stadler et al, 2006(Stadler et al, , 1999, increase microbial biomass and activity (Dighton, 1978;Choudhury, 1985), and may trigger bottom-up cascading effects on soil food webs (Seeger and Filser, 2008;Wardle et al, 2010). Yet, several studies found no support for a soil biota mediated positive feedback loop (Foster, 1984;Grier and Vogt, 1990;Wardhaugh and Didham, 2006), suggesting that the magnitude and direction of these effects may depend on the attributes of the interacting species.…”
Section: Introductionmentioning
confidence: 99%
“…In the particular case of N. staryi, this aphid is parasitised by the highly specialised parasitoid wasp Pseudephedrus longivalvus (Star y, 1995); hence, extinction of the aphid prey should likely result in the extinction of its predator. On the other hand, aphids during their feeding exude large amounts of honeydew that after being washed by rainfall reaches the ground and may provide nutrients to the ground and belowground community thus upsetting original equilibria, similarly to scale insects in Nothofagus forests (Wardle et al, 2010).…”
Section: Contributions To Current Conservation Programsmentioning
confidence: 99%